2017
DOI: 10.1080/14735784.2017.1410439
|View full text |Cite
|
Sign up to set email alerts
|

Middle East and other futurisms: imaginary temporalities in contemporary art and visual culture

Abstract: This article focuses on recent contemporary art of Gulf Futurism and Arab Futurism with a specific geographical focus on the Near and Middle East. Still only occasionally addressed and analysed in contemporary academic discussions, these art discourses and practices can be understood as particular forms of counterfuturisms and cultural politics of imaginary times; they continue the earlier work of Afrofuturism in using an aesthetic repertoire to complicate normalised notions of time and technology but in an al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The proliferation of futurisms (Arabfuturism, Asia-futurism, Gulf Futurism, Indigenous Futurisms, etc.) and the inclusion of sinofuturism among them demands careful analysis beyond the serialization of global futurisms as geopolitical aesthetics patterned on the experience of Afrofuturism (Parikka 2018).…”
Section: Global Lessons and Warnings From Sinofuturismmentioning
confidence: 99%
“…The proliferation of futurisms (Arabfuturism, Asia-futurism, Gulf Futurism, Indigenous Futurisms, etc.) and the inclusion of sinofuturism among them demands careful analysis beyond the serialization of global futurisms as geopolitical aesthetics patterned on the experience of Afrofuturism (Parikka 2018).…”
Section: Global Lessons and Warnings From Sinofuturismmentioning
confidence: 99%
“…Over the past decade or so, major media studies scholars such as Jussi Parikka (2014Parikka ( , 2015Parikka ( , 2016, Sean Cubitt (2016), and others have brought attention to the ways in which digital technologies exist at the cost of exploiting finite planetary resources and the people used to extract them for the profit of others. TikTok is not immune.…”
Section: Precarious Planetmentioning
confidence: 99%
“…The expression forms of visual art in different social environments are mostly based on cultural heritage and spiritual levels, exhibiting different intentionality and timeliness. Different artistic forms complicate the concept of visual art and demonstrate the activity of the spiritual level under artistic perception [6][7]. The above research has demonstrated the main functions of visual art in different environments, but further exploration is needed.…”
Section: Introductionmentioning
confidence: 97%